Let $f(x)=x^3-6x^2+x+4$ and $g(x)=x^5-6x+1\in \mathbb{Q}[x]$.

Find $\gcd(f,g)$ by using the Euclidean algorithm.(done)

Also use extended euclidean algorithm to find $s(x),t(x) \in Q[x]$ s.t. $\gcd(f,g)=fs+gt$. (not done)

Note that we are in $Q[x]$ land. $$\begin{aligned} x^5-6x+1 & =(x^3-6x^2+x+4)(x^2+6x+35)+(200x^2-65x-139) \\ x^3-6x^2+x+4 & =(200x^2-65x-139)\left (\frac{x}{200}-\frac{227}{8000} \right) + \left (\frac{239}{1600}x+\frac{447}{8000} \right) \\ 200x^2-65x-139 &=\left( \frac{-239}{1600}x+\frac{447}{8000} \right) \left (\frac{-3200}{239}x-\frac{375200}{57121}\right )+\frac{-7731076}{57121} \end{aligned}$$ So $\gcd(f(x),g(x))=1$

Setting up for reveres substitution

$$\begin{aligned} \frac{-7730176}{57121}& =(200x^2-65x-139) - \left (\frac{-239}{1600}x+\frac{447}{800} \right) \left ( \frac{-320000}{239}x-\frac{375200}{57121} \right) \\ \frac{-239x}{1600} +\frac{447}{8000} &= \left ( x^3-6x^2+x+4 \right) -\left ( \left (200x^2-65x -139 \right) \left ( \frac{x}{200}-\frac{227}{8000}\right) \right) \\ 200x^2-65x-139&= \left (\left (x^5-6x+1 \right ) -\left(x^3-6x^2+x+4\right)\left (x^2+6x+35 \right)\right) \end{aligned} $$ Call them 1,2,3 in decending order where 1 is constant=____

$3 \to 2$

$$ \frac{-239x}{1600} +\frac{447}{8000} = \left ( x^3-6x^2+x+4 \right) -\left ( \left (\left (x^5-6x+1 \right ) -\left(x^3-6x^2+x+4\right)\left (x^2+6x+35 \right)\right) \left ( \frac{x}{200}-\frac{227}{8000}\right) \right) $$

Running out of real state at this point but missing a step got $$\frac{-239x}{1600} +\frac{447}{8000} =(x^3-6x^2+x+4)\left (1-\left (x^2+6x+35\right) \left(\frac{x}{200}-\frac{227}{8000} \right) \right) -\left( x^5-6x+1 \right) \left (\frac{x}{200}-\frac{227}{8000}\right) $$

$2 \to 1$

$\frac{-7730176}{57121}=(200x^2-65x-139) - \left ( (x^3-6x^2+x+4)(1-(x^2+6x+35)(\frac{x}{200}-\frac{337}{800}))(\frac{-340000x}{239})-\frac{375,200}{571221} \right) + (-1)(x^5-6x+1)(\frac{x}{200}-\frac{227}{8000})(\frac{-320000x}{239}-\frac{375200}{57121}) $

Was able find the gcd but could no find the $sf+tg=1$


The answer given by WA is really horrible:

$ s=\dfrac1{120784}(-5975 x^4-2235 x^3-4879 x^2-3139 x+30835) $

$ t=\dfrac1{120784}(5975 x^2-33615 x-2556) $

No wonder you're having trouble!


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.